A Case of Pregnant Female Detected with Ampullary Carcinoma, the Course of the Disease and Pregnancy after Pancreaticoduodenectomy (Whipple’s Procedure) - Nisma M. Al Mansouri, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Ampullary and pancreatic carcinoma have high mortality rates particularly among the solid tumors. The median survival of untreated metastatic and locally advanced ampullary and pancreatic carcinoma are 3-5 and 6-10 months, respectively. The worldwide mortality due to these types of malignancies is increasing with more reported cases from the Middle East and North Africa. The incidence of ampullary carcinoma among pregnant females is rare. A limited number of cases have been reported. Here we report a case of a pregnant female detected with ampullary carcinoma, the course of the disease and pregnancy after pancreaticoduodenectomy (Whipple’s procedure).